2019
DOI: 10.1021/acs.est.9b04823
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Black Flow Electrode Enhanced Electrochemical Desalination Using Single-Cycle Operation

Abstract: Flow-electrode electrochemical desalination (FEED) processes (e.g., flow-electrode capacitive deionization), which use flowable carbon particles as the electrodes, have attracted increasing attention, holding the promise for continuous desalination and high desalting efficiency. While it is generally believed that carbon particles with abundant microporous and large specific capacitances (e.g., activated carbon, AC) should be ideal candidates for FEED electrodes, we provide evidence to the contrary, showing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(53 citation statements)
references
References 44 publications
1
52
0
Order By: Relevance
“…Electrical conductivity depends on the contact area between these particles, which is mainly limited by the shape. One possible approach is to use a conductive additive within the slurry electrodes to increase the conductivity . In this work, we used KB nanoparticles as conductive additive for the GP slurries.…”
Section: Resultsmentioning
confidence: 99%
“…Electrical conductivity depends on the contact area between these particles, which is mainly limited by the shape. One possible approach is to use a conductive additive within the slurry electrodes to increase the conductivity . In this work, we used KB nanoparticles as conductive additive for the GP slurries.…”
Section: Resultsmentioning
confidence: 99%
“…84 By sacrificing SAC for electrical conductivity (using only carbon black as the electrode material) a recent study demonstrated enhanced ASAR, scaled by the membrane area, by a factor of five. 78 Consequently, the total salt removal increased without any decrease in energy efficiency. The absolute value of energy efficiency reported in this same study, ∼8 μmol J −1 , is on the same order of magnitude as that of a standard MCDI system, 41 but we remind the reader that such comparisons are complicated by variation of experimental conditions (see section on CDI metrics).…”
Section: Configurations Advantages Disadvantagesmentioning
confidence: 99%
“…In this work, the electrodes are cycled from one half-cell to the other to allow continuous reuse of the active material. 78 Reproduced with permission from ref. 78.…”
Section: Configurations Advantages Disadvantagesmentioning
confidence: 99%
“…The first FCDI device with three chambers (i.e., one spacer and two electrode chambers) was designed and experimentally tested for seawater desalination by Jeon and co-workers in Korea in 2013 (Figure a) . The following years have witnessed a dramatic increase in the number of trials conducted to enhance the desalination performance by optimizing cell configuration and components, as well as operational modes (Figure b). , While desalination is the dominant application area for FCDI, there is an increasing number of studies related to resource recovery and contaminant abatement. …”
Section: Introductionmentioning
confidence: 99%